Development and characterization of starch nanoparticles by gamma radiation: Potential application as starch matrix filler - Lamanna, Melisa Elsa (2013)
Gamma radiation arises as an advantageous alternative to obtain starch nanoparticles given its low cost,simple methodology and scalability. Starch nanoparticles (SNP) with sizes around 20 and 30 nm were obtained applying a dose of 20 kGy from cassava (CNP-) and waxy maize (WNP-) starch, respectively. They showed the same thermal degradation behavior and their maximum mass loss zone was similar to those nanoparticles obtained from acid hydrolysis (WNP-h). Additionally, CNP- and WNP- were used as nanofillers in a cassava matrix. Increments of 102% in storage modulus were obtained with the addition of only 2.5 wt.% of WNP-, showing that gamma radiation is a successful methodology to obtain SNP able to be used as starch reinforcement.